DAMPAK BROKEN HOME PADA ANAK MUDA DAN SOLUSINYA - Juwinner Dedy Kasingku; Alan Hubert Sanger; Dinny Anggreiny Geotrida Gumolung (Universitas Pahlawan Tuanku Tambusai, 2022)
This article aims to find a good solution for children whose families are not doing well, which can affect their social life, which is what is known as a